Phenomenology as grammar - Padilla Gálvez, Jesús, 1959- (Publications of the Austrian Ludwig Wittgenstein Society ;, 2008)
This volume gathers papers, which were read at the congress held at the University of Castilla-La Mancha in Toledo (Spain), in September 2007, under the general subject of phenomenology. The book is devoted to Wittgenstein's thoughts on phenomenology. One of its aims is to consider and examine the lasting importance of phenomenology for philosophic discussion. For E. Husserl phenomenology was a discipline that endeavoured to describe how the world is constituted and experienced through a series of conscious acts. His fundamental concept was that of intentional consciousness. What did drag Witt.